KEKERASAN TERHADAP PEREMPUAN DI PENGUNGSIAN: TINJAUAN TEORITIS DAN TEMUAN STUDI LITERATUR - Vikila Diyah Arita (Jurnal Humaniora & Sosial Sains, 2025)
Violence against women in refugee camps remains a serious problem due to gender inequality, weak protection, and limited access to human rights. This study aims to identify the forms of violence experienced by refugee women, the causal factors, the impacts, and the necessary protection strategies. Using qualitative methods based on literature, this study analyzed various sources such as journals, research reports, and policy documents. The results indicate that refugee women experience physical, psychological, and sexual violence. The main causes include unequal power relations, gender stereotypes, and limited protection systems in refugee camps. The impact of violence is multidimensional, ranging from health problems and psychological trauma to social marginalization. Therefore, women's protection must be placed within a human rights framework with comprehensive strategies, such as establishing safe refugee camps, providing special protection spaces, providing medical and psychosocial services, and strengthening community participation. Collaboration between the government, humanitarian agencies, law enforcement officials, and refugee communities is necessary to achieve effective and sustainable protection.